Pemanfaatan Eceng Gondok Sebagai Pakan Ternak Fermentasi Untuk Pengurangan Biaya Pakan Ditingkat Peternak Kecil Kkn Universitas Pekalongan Di Kelurahan Krapyak - Khoirima Fitriana; Imam Saefudin Fajar; Khoirunnisa Nabila; Siska Ayu Melati; Muhammad Hanif; Sella Purwanda; M. Ardi Yahya; Noor Lailatus Sa’diyah; Ibnu Figo Dewa Candra; Laelatul Khoiriyah Arrosyid; Laila Mahfiroh; Tri Yusufi Mardiana (CV. SINAR HOWUHOWU, 2025)
This community service program addresses two interrelated problems in Krapyak Village, Pekalongan City, namely the uncontrolled growth of water hyacinth in rivers and the high cost of animal feed for small farmers. The aim of this program is to utilize water hyacinth as a raw material for fermented animal feed, thereby reducing feed costs and controlling weed growth in waterways. The implementation involves several stages, namely field observation, coordination with the village administration, conducting trials of fermented feed using a mixture of water hyacinth, rice bran, molasses, and EM4, as well as providing education and direct application to local farmers. The program ran from December 30, 2025, to January 2, 2026, targeting farmers in Krapyak Village. The results showed that the fermentation process produced feed with good physical qualities, such as crumbly texture, brownish color, and a slight sour aroma, indicating that the fermentation was optimal. This program has a positive economic impact, namely reducing dependence on expensive conventional feed, as well as an environmental impact, namely controlling the growth of water hyacinth in rivers. This initiative offers a sustainable solution in line with the principles of the circular economy, namely converting environmental waste into useful resources, which supports the welfare of farmers and maintains the sustainability of the ecosystem.